GE_GERICHTE P/1975/2018 vom 25. September 2018 - GE Cour de justice (2018)
INFRACTIONS CONTRE LE PATRIMOINE ; INFRACTIONS CONTRE L'HONNEUR ; DÉNONCIATION CALOMNIEUSE | CPP.310; CP.137; CP.138; CP.173; CP.174; CP.303